Development and Implementation of an Opioid Overdose Prevention and Response Program in Toronto, Ontario - Leece, Pamela N. (Can J Public Health, 2013)
OBJECTIVES: We describe the development of the first community-based opioid overdose prevention and response program with naloxone distribution offered by a public health unit in Canada (Prevent Overdose in Toronto, POINT). PARTICIPANTS: The target population is people who use opioids by any route, throughout the City of Toronto. SETTING: The POINT program is operated by the needle exchange program at Toronto Public Health (The Works) and offered at over 40 partner agency sites throughout Toronto. INTERVENTION: POINT is a comprehensive program of overdose prevention and response training, including naloxone dispensing. Clients are instructed by public health staff on overdose risk factors, recognizing signs and symptoms of overdose, calling 911, naloxone administration, stimulation and chest compressions, and post-overdose care. Training is offered to clients one-on-one or in small groups. Clients receive a naloxone kit including two 1 mL ampoules of naloxone hydrochloride (0.4 mg/mL) and are advised to return to The Works for a refill and debriefing if the naloxone kit is used. OUTCOMES: In the first 8 months of the program, 209 clients were trained. Clients have reported 17 administrations of naloxone, and all overdose victims have reportedly survived. Client demand for POINT training has been high, and Toronto Public Health has expanded its capacity to provide training. Overall, reception to the program has been overwhelmingly positive. CONCLUSION: We are encouraged by the initial development and implementation experience with the naloxone program and its potential to save lives in Toronto. We have planned short-, intermediate-, and long-term process and outcome evaluations.